Stuck in the middle is fiscal policy failing the middle class? - Estache, Antonio; Leipziger, Danny M.; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2009)
"Examines both economic and social public policy initiatives in its assertion that enhancing the welfare of people in developed and developing nations requires an explicit focus on the middle class"--Provided by publisher.
Foreword -- Overview : fiscal policy, distribution, and the middle class / Antonio Estache and Danny Leipzinger -- Stylized facts on the middle class and the development process / Andres Solimano -- The future of global income inequality / Maurizio Bussolo, Rafael E. De Hoyos, and Denis Medvedev -- The scope and limits of subsidies / Markus Goldstein and Antonio Estache -- Policies for lower global wealth inequality / James Davies -- Can happiness research help fiscal policy? / Carol Graham -- The politics of effective and sustainable redistribution / Evelyne Huber, Jennifer Pribble, and John D. Stephens -- Contributors.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Fiscal policy -- Case studies; Middle class -- Government policy -- Case studies; Electronic books